2011
DOI: 10.1902/jop.2010.100348
|View full text |Cite
|
Sign up to set email alerts
|

The Periodontal Examination Profile of General Dentists in Nova Scotia, Canada

Abstract: Although the majority of dentists in our study report performing periodontal examinations of their patients, only a small portion report recording complete probing depth measurements or using appropriate radiographs in their examinations. These practices could lead to an underestimation of diagnosis and treatment of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(78 citation statements)
references
References 13 publications
8
67
3
Order By: Relevance
“…First, there is the role of the GDP as the primary screening and referral source. Studies carried out from 2006 to 2013 have found an increasing tendency for GDPs to retain periodontal cases in‐house for non‐surgical care and maintenance 14 , 17 , 18 . A study reviewing American practices found that 90% of SRP procedures were conducted by GDPs during 2005 to 2006 compared with 25% in 1990, with 10% and 75%, respectively, being seen by periodontists 14 .…”
Section: Discussionmentioning
confidence: 99%
“…First, there is the role of the GDP as the primary screening and referral source. Studies carried out from 2006 to 2013 have found an increasing tendency for GDPs to retain periodontal cases in‐house for non‐surgical care and maintenance 14 , 17 , 18 . A study reviewing American practices found that 90% of SRP procedures were conducted by GDPs during 2005 to 2006 compared with 25% in 1990, with 10% and 75%, respectively, being seen by periodontists 14 .…”
Section: Discussionmentioning
confidence: 99%
“…While differentiating health from destructive periodontal disease is simple at the professional level, relying on clinical presentation to differentiate these diseases, particularly at the earliest stages of initiation and/or progression remains challenging for clinicians (16). The development and implementation of modern technologies that can provide rapid, non-invasive, screening diagnoses that can be applied in a broader health care setting, and/or put into practice for “high risk”, historically underserved populations lacking well developed medical/dental support systems, would be a substantial benefit to improving oral and systemic health.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with other qualitative studies which found high proportions of dentists were confident in their ability to diagnose periodontal disease but less so in treating it. [18][19][20] Some of the barriers identified, such as motivation of patients and time and money, are also reflected in previous studies, 6,21 with dentists reporting the treatment provided was significantly influenced by the NHS remuneration system. 22 Habit and routine was highlighted as a barrier in a series of audits of a system 23 designed to assist dentists by giving them prompts to conduct a periodontal examination.…”
Section: Discussionmentioning
confidence: 70%